The Mass Media News Framing Analysis of Polemic of Regulations on Prevention and Handling Sexual Violence in Higher Education - Ratih Anbarini; Adry Alim Priyatna; Annisa Nursalsabillah; Marlia Marlia (ARISTO, 2023)
Regulation of the Minister of Education, Culture, Research, and Technology (Permendikbudristek) Number 30 of 2021 concerning the Prevention and Handling of Sexual Violence (Pencegahan dan Penanganan Kekerasan Seksual/PPKS) in Higher Education, which was signed in August 2021, raises pros and cons in society. The phrase "without the victim's consent" is considered to promote free sex in the campus environment. Then the mass media was busy reporting the issue. Some media think the regulation needs to be supported. However, there are also media outlets that urge the need for revisions to the polemical use of the phrase. This study examines how mass media with different ideologies frame the issue of Permendikbudristek PPKS. Using Robert M. Entmen's framing analysis and the theory of social reality construction, this study analyses the polemic coverage of the Permendikbudristek PPKS period 5 to d. November 12 2021 in Republika and Koran Tempo. The results showed that the ideologies adopted by Republika and Koran Tempo were different, thus constructing the Permendikbudristek reporting differently.